Cochrane Review Summaries—April 2021. Issue 4 (April 2021) - Cohen, Megan; Edelman, Alison; Bellussi, Federica; Berghella, Vincenzo; Haas, David M.
Abstract : In this month's issue, the journal continues to bring new insights from Cochrane Systematic Reviews to the readers of Obstetrics & Gynecology . This month, we highlight the use of self-administered medication for abortion, antibiotic use during operative vaginal delivery, and timing of labor induction. The summaries are published below. The complete references with hyperlinks are listed in Box 1.